Dampak Inovasi Kapal Otonom Jepang Terhadap Hubungan Maritim Dengan Negara-Negara ASEAN - Florencia Caroline; Imran Hanafi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Technological innovations in autonomous vessels developed by Japan, such as the MEGURI2040 project, have opened up great opportunities in improving maritime efficiency and strengthening economic ties with ASEAN countries. These technologies offer operational advantages through cost reduction, route optimization, and enhanced maritime safety, which can promote economic integration in the region. However, the adoption of autonomous ships also presents challenges, including the need for regulatory harmonization, port infrastructure improvement, and cybersecurity risk management. This study analyzes the impact of autonomous ship innovation on the logistics sector, workforce, maritime safety, and the potential for technological cooperation between Japan and ASEAN. The results show that the adoption of this technology can strengthen regional cooperation, but requires technical readiness, mature regulations, and multilateral collaboration to overcome emerging challenges. Therefore, the integration of autonomous ship technology in ASEAN requires not only a strategic approach, but also a shared commitment to create stability and sustainable economic growth in the region.